Yield and Quality of Buffalo Milk in Semi-intensive and Intensive farming in Mymensingh District of Bangladesh - Md Mahedi Hasan Bindu; Md Monoarul Islam; Sonia Sharmin; Md Nurul Islam; S M Rajiur Rahman; Md Abunaser; Elena Hoque Raka; Mohammad Ashiqul Islam (Research in Agriculture Livestock and Fisheries, 2025)
This study aimed to compare the buffalo milk yield and quality under semi-intensive and intensive management in village conditions. During the experiment, day-to-day milk production was recorded. pH, Acidity, Total solids, Specific gravity, Milk fat, Solids not fat, Lactose, Mineral, and standard plate count were evaluated. The average daily milk yield (L/d) of buffaloes under semi-intensive practice and intensive groups were 2.84 and 4.48 L/d, respectively, which were significantly different (p<0.01) from each other. There was a significant difference (p<0.05) in specific gravity of milk, milk fat percentage, acidity, and pH of milk between the two management systems. The efficiency of milk production was significantly (p<0.05) higher in intensive systems than semi-intensive systems. In case of microbial quality, buffalo milk from semi-intensive system (5.97±0.84) log CFU/ml resulted significantly (p<0.05) higher standard plate count than intensive system (5.85±0.06) log CFU/ml. The result of the experiment showed better performance of buffalo in intensive conditions rather than semi-intensive in terms of milk quality and yield. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 01-06